The Comparison of Fine Needle Aspiration Cytology and Histopathology Results in Hypoactive Solitary Thyroid Nodule - Gelıncık, İbrahim (Fırat University, 2013)
Objective: Fine-needle aspiration (FNA) is currently the primary diagnostic procedure in diagnosing thyroid malignancy and guides surgeons on patient selection for thyroidectomy for thyroid nodules. Based on the cytology findings, patients can be followed in cases of benign diagnosis or subjected to surgery in cases of malignant diagnosis thereby decreasing the rate of unnecessary surgery. Purpose of the present study was to correlate the fine needle aspiration cytology (FNAC) findings with histopathology of excised specimens. Materials and Methods: A comprehensive view of hospitalization records was performed that have assessed the sensitivity of FNA for detecting thyroid malignancy in hypoactive solitary thyroid nodules. This was a prospective study conducted on 62 consecutive patients between December 2001 and June 2008. All patients with clinically diagnosed solitary thyroid nodule who were clinically, radyologically and biochemically hypothyroid were included for study. Patients with multinodular goitre, euthyroid and hyperthyroid were excluded from the study. Results: The sensitivity, specificity, accuracy, false positive rate, false negative rate, positive predictive value, and negative predictive value of FNAC for the diagnosis of neoplastic hypoactive solitary thyroid nodules were 80,7 %, 88,8 %, 85,4 %, 11,1%, 19,2 %, 80,7 %, and 88,8 %, respectively. The most common malignancy detected was papillary carcinoma of thyroid in 8 patients. Conclusion: Fine needle aspiration cytology is a simple, easy to perform, cost effective, and easily repeated procedure for the diagnosis of thyroid cancer. It is recommended as the first line investigation for the diagnosis of hypoactive solitary thyroid nodule.

Amaç: İnce iğne aspirasyonu tiroid malignensilerinin teşhisinde halen ilk akla gelen bir yöntemdir ve tiroid nodülü bulunan, tiroidektomi yapılacak olan hastaların seçiminde cerraha yol gösterir. Sitolojik bulgulara göre, hastalar benign olarak teşhis edildiklerinde takip edilebilir veya malign olarak tehis edildiklerinde opere edilebilirler. Böylece gereksiz cerrahiden kaçınılmış olur. Bu çalışmanın amacı ameliyat materyallerinin histopatolojisi ile ince iğne aspirasyon sitolojisi bulgularının ilişkisini araştırmakdır. Gereç ve Yöntem: Hipoaktif soliter tiroid nodüllerinde tiroid maliğnensilerinin tespiti için hastane kayıtları kapsamlı bir şekilde gözden geçirilerek tiroid ince iğne sensitivitesi değerlendirildi. Bu 2001 Aralık'tan 2008 Haziran'a kadarki ardışık 62 hasta üzerinde yapılan bir prospektif çalışmaydı. Klinik olarak soliter tiroid nodülü teşhis edilen, klinik, radyolojik ve biyokimyasal olarak hipotiroidik olan tüm hastalar çalışmaya dahil edildi. Multinodüler guatr, ötiroid ve hipertiroidli hastalar çalışmaya dahil edilmedi. Bulgular: Neoplastik hipoaktif soliter tiroid nodüllerinin teşhisi için yapılan ince iğne aspirasyon sitolojisinin sensitivite, spesifite, doğruluk oranı, yalancı pozitiflik, yalancı negatiflik, pozitif kestirim değeri ve negatif kestirim değeri sırasıyla 80,7 %, 88,8 %, 85,4 %, 11,1%, 19,2 %, 80,7 %, ve 88,8 % idi. Sekiz hastada tespit edilen en sık malignite tiroidin papiller karsinomu idi. Sonuç: İnce iğne aspirasyon sitolojisi tiroid kanserlerinin teşhisinde basit, kolay yapılan, etkili ve kolay tekrarlanan bir yöntemdir. İnce iğne aspirasyon sitolojisi hipoaktif soliter tiroid nodüllerinin malignite açısından teşhis edilmesinde ilk olarak akla getirilmelidir.
Hipoaktif Soliter Tiroid Nodüllerinde İnce İğne Aspirasyon Sitolojisi ve Histopatolojik Sonuçların Karşılaştırılması